THEORETICAL BASIS OF ESTIMATING THE FINANCIAL STABILITY OF HOUSEHOLD - Сидорчук, Анатолій (SWorldJournal, 2022)
Based on the analysis of literature sources, the paper considers the theoretical aspects of estimating the financial stability of households. According to the proposed principles, the methodological tools for assessing the household’s financial condition